The obstacles of synergy in schools - Toremen, Fatih; Karakus, Mehmet (Edam, 2007)
The present study aimed to determine the obstacles in creating effective teamwork and generate suggestions for overcoming these obstacles. The study was designed on the basis of qualitative research approaches and used purposive sampling. Data were collected by semi-structured interviews from 52 teachers who were working at a primary school in downtown Sirnak during the autumn semester in the 2005-2006 academic year. Results showed that there were serious problems at every dimension examined except for the dimensions of different personal characteristics and applications. The following matters are counted for causing the problems: Inefficiencies in the educational system, ineffective operations of the administrators, communication and orientation problems among teachers, low levels of job satisfaction, and prejudicial attitudes. In order to resolve these problems, teachers suggested to create a team spirit, make the group more cohesive; arrange more social and cultural activities, resolve status conflicts among teachers, provide teachers with necessary resources, increase teacher motivation, accommodate norms in the school culture, and stabilize school structure.
Keywords: team work; interrelationship between individuals; synergy; communication